Induction Chemotherapy for Advanced Head and Neck Cancer Patients: Outcomes of A Quasi-Experimental Study. (Faridpur Medical College Journal, 2017)
A quasi experimental study was conducted on outcomes of Induction Chemotherapy for advanced head and neck cancer patients from October 2015 to September 2016 at Faridpur Medical College Hospital, Faridpur. A total of 40 patients with Stages T3/T4, N0-N3, M0 and histological proved Squamous cell carcinoma of the head & neck (SCCHN) were selected to receive three cycles of chemotherapy prior to loco-regional primary concurrent chemoradiotherapy (CCRT). The induction chemotherapy regimen was a combination of Inj. paclitaxel and Inj cisplatin. The primary end point of study was clinical outcome of the patients. The response rate to induction chemotherapy was 55% for the primary tumor (CR: 12% and PR: 43%). Complete disappearance of the primary tumor occurred more often than that of the lymph node metastases. The response rate to induction chemotherapy for lymph node metastases was 24% (CR: 10% and PR: 14 %).Faridpur Med. Coll. J. Jul 2016;11(2): 54-57